O Programa de Aquisiç\~ao de Alimentos da Agricultura Familiar (PAA) e as práticas dos agricultores participantes orientadas ao mercado: Estudo de caso no estado de sergipe - Danuta Chmielewska; Darana Souza; Acácio Alvarenga Lourete (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– An essential question about policies that aim to foster socio-economic inclusion and income generation - which is the case of policies that support market access - is their capacity to guarantee a sustainable process of the economic capacities of their beneficiaries. In this study, the Brazilian Food Acquisition Programme (PAA) is discussed from this angle, since it offers, among other benefits, an optional market opportunity for targeted food producers. In this case study, conducted in the state of Sergipe, two modalities of PAA that promote links between family farmers' production and local demands through public procurement were considered (CDLAF and CPR-Donation). Our analysis suggests that by offering an important commercial possibility to producers, the PAA plays a significant role in improving their market capabilities, as it promotes a variety of changes in their productive and organizational practices. These changes are due to more regular and predictable access to advantageous market, facilitated by procurement at pre-set purchase prices. Nevertheless, even if the development of these capabilities is essential to facilitate producers' participation in agricultural markets, it is not sufficient to promote further market access, since PAA is currently seen by most of these farmers as the best market channel available.
Keywords: I3; I38; Q18; 330